A Review: Immunomodulator Effects of Plants Extract on Rats with Haematological Parameter include White Blood Count and Differential Leucocytes Count - Rafika Hayu Pratiwi; Tita Juwitaningsih (Universitas Negeri Medan, 2023)
Plants extract as immunomodulatory is substance which can stimulates or suppresses the component of immune system including white blood count and differential leucocytes count. The modulation of immune system by various plants extract has become subject for scientific investigation currently worldwide. Some of these plants have been claimed to increase immune system by increasing the total white blood count and differential leucocytes count are Achyranthes aspera Linn, Cermai Leaves (Phyllanthus acidus (L.)) Skeels, Moringa oleivera and Poguntano herb (Picriafel-terraeLour).. Plants extract were recommended for us as immunomodulatory because there are several botanical products with potential therapeutic applications such as high efficacy, low cost and low toxicity.